2022
DOI: 10.1111/joor.13331
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of anxiety and depression among different subtypes of temporomandibular disorder: A systematic review and meta‐analysis

Abstract: Background The evidence on the relationship between anxiety and depression and patients with distinct subtypes of temporomandibular disorder (TMD) is uncertain, so a thorough review study on the topic is still missing. Objectives This systematic review investigated the distribution and severity of anxiety and depression in patients diagnosed with different subtypes of TMD. Methods The study is registered in PROSPERO (CRD42020150562) and it followed the PRISMA 2020 Statement. We searched in PubMed, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 59 publications
(277 reference statements)
3
33
2
2
Order By: Relevance
“…Previous systematic reviews have already revealed this positive association between TMD and psychosocial factors. Recently, Reis et al ( 18 ) demonstrated the relationship between distinct subtypes of TMD and anxiety and depression. These results suggest that patients with myofascial pain are more anxious and more depressed than patients with other subtypes of TMD, especially disc displacement or arthralgia/degenerative joint disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews have already revealed this positive association between TMD and psychosocial factors. Recently, Reis et al ( 18 ) demonstrated the relationship between distinct subtypes of TMD and anxiety and depression. These results suggest that patients with myofascial pain are more anxious and more depressed than patients with other subtypes of TMD, especially disc displacement or arthralgia/degenerative joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review ( 18 ) investigated whether there is a subtype of temporomandibular disorder that is more associated with the occurrence and severity of both anxiety and depression (together in the same patient) and the authors concluded that patients with myofascial pain are more anxious and depressed than others. In this way, it is clear how necessary to investigate separately biopsychosocial factors during the evaluation of TMD patients ( 5 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the augmented pain in the joint area reported by people in the questionnaire. This research did not include other factors usually related to TMD such as psychological distress and sleep disturbances (22,23) as well as possible previously diagnosed structural and anatomical anomalies related to the TMJs (24,25) which may in uence the orofacial pain. Some limitations may still be linked to the online survey delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Erkenntnisse über die Beziehung zwischen Angst und Depression und CMD zeigt eine aktuelle Studie, welche aufgrund einer Metaanalyse mit über 3500 Probanden zeigte, dass Patienten mit myofaszialen Schmerzen ängstlicher und depressiver sind als Patienten mit anderen Subtypen von CMD [22]. Grundsätzlich finden sich laut einem weiteren Übersichtsartikel klinisch signifikante Angstzustände und Depressionen bei Patienten mit chronischen Schmerzen im Gesichtsbereich [23].…”
Section: Diskussionunclassified